What can we learn from international comparisons of health systems and health system reform? - Barbara McPake; Anne Mills
Most commonly, lessons derived from comparisons of international health sector reform can only be generalized in a limited way to similar countries. However, there is little guidance as to what constitutes "similarity" in this respect. We propose that a framework for assessing similarity could be derived from the performance of individual policies in different contexts, and from the cause and effect processes related to the policies. We demonstrate this process by considering research evidence in the "public-private mix", and propose variables for an initial framework that we believe determine private involvement in the public health sector. The most influential model of public leadership places the private role in a contracting framework. Research in countries that have adopted this model suggests an additional list of variables to add to the framework. The variables can be grouped under the headings "demand factors", "supply factors", and "strength of the public sector". These illustrate the nature of a framework that could emerge, and which would help countries aiming to learn from international experience.